Be Still and You Will Know: A Mixed-Method Study on Solitude and Consideration of Future Consequences Among Youth in Rehabilitation - Poon, Cyanea Y. S. (International journal of offender therapy and comparative criminology, 2023)
Although solitude is found to be undesirable to many, systematic practice of it can yield positive psychological outcomes. This mixed-method study explored the process and influence of solitude as a behavioral intervention among youths in a therapeutic community in Hong Kong. Qualitative interviews with 43 youths (67.4% male, mean age = 18.3) revealed that solitude facilitated growth in their sense of personal responsibility, increased perspective-taking, increased respect for rules, change in life attitudes, and growth in consideration of future consequences. A two-wave prospective study (n = 79, 82.3% male, mean age = 17.4) further demonstrated perceived meaningfulness in solitude predicted an increase in consideration of future consequences, but not in other types of behavioral intervention. This study preliminarily demonstrated solitude has beneficial outcomes among high-risk youths, and meaning-making can facilitate this relationship.